2009
DOI: 10.1089/apc.2008.0143
|View full text |Cite
|
Sign up to set email alerts
|

Genital and Perianal Herpes Simplex Simulating Neoplasia in Patients with AIDS

Abstract: Genital and perianal herpetic ulcers are common in HIV-infected patients and chronic mucocutaneous ulcers persisting for more than 1 month are the hallmark of active AIDS status. However, atypical clinical manifestations of herpes simplex virus (HSV) may occur in immunocompromised patients presenting as tumor-like nodules or condylomatous or hypertrophic lesions, rather than a classic ulcer. Such unusual presentations raise the risk of misdiagnosis and a delay in appropriate treatment. Here we describe nine im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…Wart-like CHSV and CVZV infections may mimic a number of benign or malignant growths, 61,107 including keratoacanthoma, HPV-related verrucous lesions, 93 condylomata acuminata and lata, 66 basal cell carcinoma, 82 verrucous carcinoma, 101 and squamous cell carcinoma. 56,57 Ulcerative CHSV and CVZV may resemble other ulcerations, including genital herpes, CMV-related ulcerations, perianal longstanding herpes in bedridden patients, 109 Hailey-Hailey disease, pemphigus vulgaris, syphilis, Haemophilus ducreyi, extraintestinal Crohn's disease, rectocolitis, and Behçet disease.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Wart-like CHSV and CVZV infections may mimic a number of benign or malignant growths, 61,107 including keratoacanthoma, HPV-related verrucous lesions, 93 condylomata acuminata and lata, 66 basal cell carcinoma, 82 verrucous carcinoma, 101 and squamous cell carcinoma. 56,57 Ulcerative CHSV and CVZV may resemble other ulcerations, including genital herpes, CMV-related ulcerations, perianal longstanding herpes in bedridden patients, 109 Hailey-Hailey disease, pemphigus vulgaris, syphilis, Haemophilus ducreyi, extraintestinal Crohn's disease, rectocolitis, and Behçet disease.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…1 However, atypical, fungating vulval lesions due to HSV are rare but have been reported. [1][2][3][4][5][6] HSV lesions may present as large fungating, hypertrophic lesions that present both diagnostic and treatment challenges and may necessitate repeated biopsies and cultures. 3 In this patient, the initial punch biopsy of the vulval mass revealed herpes simplex infection.…”
Section: Evidence-based Opinionmentioning
confidence: 99%
“…Other forms of therapy have included the use of imiquimod 6 and surgical excision with oral acyclovir. 1 Studies have suggested that hypertrophic genital lesions due to HSV may be related to acyclovir resistance. 1,2 In this case study, a moderate response was seen when intravenous acyclovir was used.…”
Section: What Treatment Would You Consider Based On Your Suspected DImentioning
confidence: 99%
See 1 more Smart Citation
“…3 The presence of HSV in the lesion can be demonstrated either by immunohistochemistry, direct immunofluorescence, viral cultures or molecular biology techniques.…”
Section: Discussionmentioning
confidence: 99%